Population Dynamics and Biomass of Hymenoptera in a Temperate Grassland - Joshi, P. C. (Indian Forester, 1997)
The role of Hymenoptera in pollinating the flowers is well recognised, they appear to have an important influence on other parts of the grassland ecosystem by supplying food for consumers. The other important function of these insects is the transfer of nutrients and energy from the primary producers to the decomposers.